Peran dan Komitmen Indonesia dalam “Millenium Development Goals”: (Perspektif Humas Internasional) - Yuningsih, Ani (Mediator, 2007)
The Declaration of Millenium Development Goals (MDGs) marked a new context in global network which emphasized the role of present society toward the future of next generation. Within MDGs scheme, wealthy countries are encouraged to help their counterpart—underdevelopment countries—by donating some funds for developing their countries. Indonesia’s commitment toward MDGs was expressed by publicity means such as campaign, slogans, etc. Such actions are not enough. The commitment of Indonesia government toward MDGs as seen from International Public Relation Perspective must be implemented through a series of effort to cut poverty, which involved every citizen and stakeholders. Based on national information system, penetrated to structural and functional layers, program socialization and education could reach a maximum impact.